FRI0176 PHASE 2, DOUBLE-BLIND, RANDOMIZED, PLACEBO-CONTROLLED STUDY OF A REVERSIBLE B CELL INHIBITOR, XMAB®5871, IN SYSTEMIC LUPUS ERYTHEMATOSUS (SLE). (June 2019) - Merrill, Joan; June, Joshua; Koumpouras, Fotios; Machua, Wambui; Khan, Mohammad Faisal; Askanase, Anca; Khosroshahi, Arezou; Sheikh, Saira; James, Judith A.; Guthridge, Joel; Rathi, Gaurav; Burington, Bart; et al.
Abstract : Background: XmAb5871 is a humanized anti-CD19 antibody Fc-engineered for increased affinity to FcγRIIb. Co-ligation of CD19 and FcγRIIb inhibits B lineage cells key to SLE pathogenesis. Objectives: This Phase 2 study was designed to minimize background medications and placebo responses to improve interpretation of a small trial in a complex, heterogenous disease. Methods: SLE patients were enrolled with active disease, ameliorated during screening with ≥160 mg of IM Depo-Medrol. Improvement was required before randomization, defined by decrease in SLEDAI ≥4 points or ≥1 grade in a BILAG A or B score. Immunosuppressive drugs were stopped except antimalarials and/or ≤10 mg/day prednisone or equivalent. Subjects were randomized to IV XmAb5871 (5 mg/kg) or placebo and given Depo-Medrol 80 mg IM on Days 1 and 15, after which, steroid impact was expected to withdraw gradually. Study treatments were given Q14 days for up to 16 doses or loss of improvement (LOI ), defined as SLEDAI increase ≥4 points OR new BILAG A or B, with investigator-determined significance. At LOI, patients could receive immediate standard treatments. The primary endpoint was the proportion with no LOI by Day 225 in the efficacy evaluable group (those completing Day 225 or withdrawn for LOI or drug-related adverse event). Results: 104 subjects were randomized: 99 female, median age 45 (20-65). The primary endpoint was met by 21 (42%) of XmAb5871-treated patients vs 12 (28.6%) of the placebo group (p=0.18). All but one responder also fulfilled the SRI-4 response definition from screening to completion. Results did not differ in those with or without anti-dsDNA and/or ENA antibodies. Time to flare was significantly longer in the XmAb5871 group (p=0.025) (figure 1 ) . XmAb5871-treated patients with LOI had less recurrent disease after IM steroid cessation than those in the placebo group; 6 (20%) of placebo patients developed BILAG A scores vs 3 (13%) in the active arm. 9 (30%) of worsening placebo patients had SLEDAI increase ≥7 vs 0 in the XmAb5871 group. SLEDAI scores were higher and increased sooner after disease nadir with placebo vs XmAb5871 (figure 2 ) ; 16 (30.8%) of XmAb5871 patients vs 7 (13.5%) placebo patients sustained LLDAS (low disease) during months 6-8 (p=0.0453). Transient, infusion-related gastrointestinal side effects occurred in XmAb5871-treated patients during the 1st or 2 nd infusion. There were 8 SAEs in 7 XmAb5871-treated subjects, 5 in 4 placebo patients, no opportunistic infections, and no deaths. Infection rate was low compared to other SLE trials. Conclusion: XmAb5871 was well-tolerated. Preliminary data from this small trial indicates suppression of disease recurrence after treatment withdrawal, supporting further evaluation of XmAb5871 in SLE. Disclosure of Interests: Joan Merrill Grant/research support from: Genentech, UCB, GSK, EMD Serono, Pfizer, Celgene, Exagen, Bristol Myers Squibb, Medimmune/Astra Zeneca, Lilly, Amgen, Xencor, Neovacs, Consultant for: Genentech, UCB, GSK, EMD Serono, Pfizer, RemeGen, Celgene, Exagen, Bristol Myers Squibb, Medimmune/Astra Zeneca, Lilly, Immupharma, Amgen, Janssen, Sanofi, Neovacs, Anthera, Speakers bureau: UCB, GSK, EMD Serono, Bristol Myers Squibb, Medimmune/Astra Zeneca, Janssen, Joshua June: None declared, Fotios Koumpouras: None declared, Wambui Machua: None declared, Mohammad Faisal Khan: None declared, Anca Askanase: None declared, Arezou Khosroshahi: None declared, Saira Sheikh: None declared, Judith A. James: None declared, Joel Guthridge: None declared, Gaurav Rathi Shareholder of: Xencor Inc, Employee of: Xencor Inc, Bart Burington Shareholder of: Xencor Inc, Employee of: Xencor Inc, Paul Foster Shareholder of: Xencor Inc, Employee of: Xencor Inc, Debra Zack Shareholder of: Xencor Inc, Employee of: Xencor Inc